Environmental Citizenship and Youth Activism - Reis, Pedro (2020)
The exercise of Environmental Citizenship is strongly associated with a citizen’s capacity to act in society as an agent of change (ENEC 2018), and this depends on the development of a person’s willingness and competence for a critical, active and democratic engagement in preventing and solving environmental problems. There is a call for a citizenry that is well informed and empowered to take appropriate actions on the seriousness of the environmental problems affecting our world (Gray et al. 2009; Hodson 2003). However, many citizens do not feel empowered enough to participate in decision-making processes regarding socio-environmental issues, and, at the same time, the faith and trust in politicians have decreased, and political apathy is gaining ground (Hodson 2014). Throughout the past decade, the surge in authoritarian government practices, the failure of popular movements to replace undemocratic regimes and the increase in populist movements all over the world are fuelling concerns about a possible ‘democratic recession’ (Diamond 2015). Part of the success of this movement has been credited to the failures in mobilising young people’s political participation (Schulz et al. 2018; Jackson et al. 2016). Civic engagement depends on students and their ‘motivation to participate in civic activities, their confidence in the effectiveness of their participation, and their beliefs about their own capacity to become actively involved’ (Schulz et al. 2018, p. 72). Research shows that a student’s civic engagement can be supported and encouraged by school, with the help of (1) open school climates, (2) democratic structures within schools and (3) early opportunities for active participation, the promotion of students’ civic knowledge and the predisposition to engage in civic activities in the future (Schulz et al. 2018; Pancer 2015; Roth and Barton 2004). Therefore, education represents a key element in counteracting low levels of civic engagement among young people, namely, through the promotion of democratic activism (Hodson 2014).